The Merging Cooperatives Based on The Regulation of Cooperatives and Job Creation - Dewi Sulistianingsih; Hendri Januar Romadhon; Pujiono Pujiono (Law and Justice, 2021)
This paper aims to describe and analyze the procedure for merging cooperatives in Indonesia based on applicable regulations and the legal consequences of merging these cooperatives. Cooperative is a form of cooperation in the economic area. Cooperation in cooperatives is generally conducted under the same goal: the necessities of life. In industrialized countries, cooperatives emerged as a reaction to the system of economic freedom in the 19th century, where a group of capital owners controlled people's lives. Cooperatives in several countries have merged to increase the existence and efficiency of improving their welfare. In Indonesia, the merger of cooperatives is necessary when the cooperative wants efficiency to improve welfare. Based on the study results, it can be seen that merging cooperatives was carried out to improve the welfare of members. The act of merging cooperatives was carried out with the legal provisions in Law Number 25 of 1992. It did not use the existing rules in the Law of the Republic of Indonesia No. 11 of 2020 on Job Creation.